1997
DOI: 10.1152/ajpregu.1997.272.4.r1258
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status and lipid peroxidation after short-term maximal exercise in trained and untrained humans

Abstract: The purpose of this study was to measure resting muscle and blood antioxidant status in untrained (n = 8) and jump-trained (n = 8) humans and to evaluate free radical-mediated muscle damage after a strenuous jump test consisting of six bouts of 30-s continuous jumping separated by 2 min of rest. Resting muscle antioxidant activities [superoxide dismutase (SOD), glutathione peroxidase (GPX), glutathione reductase (GR), and manganese SOD] were significantly higher in jump-trained compared with untrained subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
1
14

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 0 publications
11
70
1
14
Order By: Relevance
“…The chronic training promotes definitive increases in these defences. Additionally, Brites et al (1999) and Ortenblad et al (1997) found that trained human athletes had higher baseline concentrations of this enzyme than did untrained individuals, which is in accordance with the results of the present study maybe because, according to new FEI rules for the horses competing in 80km races, they must be graduated first, so they necessarily trained for at least two years.…”
Section: Resultssupporting
confidence: 91%
“…The chronic training promotes definitive increases in these defences. Additionally, Brites et al (1999) and Ortenblad et al (1997) found that trained human athletes had higher baseline concentrations of this enzyme than did untrained individuals, which is in accordance with the results of the present study maybe because, according to new FEI rules for the horses competing in 80km races, they must be graduated first, so they necessarily trained for at least two years.…”
Section: Resultssupporting
confidence: 91%
“…These antioxidants are produced by skeletal muscles [53]. Repetitive training can increase antioxidant synthesis and activity in cells and healthy people [58,59].…”
mentioning
confidence: 99%
“…Many studies have compared the antioxidant status of trained and untrained subjects at rest (Ørtenblad et al, 1997;Balakrishnan & Anuradh 1998;Brites et al, 1999;Evelson et al, 2002;Cazzola et al, 2003;Gougoura et al, 2007;Yamaner, 2010), but, to our knowledge, except the study of Ørtenblad and coworkers (1997) that analyzed blood antioxidant status in untrained and jump-trained humans following six bouts of 30-s continuous jumping, no study has compared the athletes' and non-athletes' pro/antioxidant responses to acute exercise of maximal intensity. The hypothesis of the first part of that study was that athletes would have not only higher activity of antioxidants in rest, but that the extent of redox disturbance induced by a maximal progressive exercise test would be lower in athletes compared with non-athletes.…”
Section: Comparison Of Blood Pro/antioxidant Levels Before and After mentioning
confidence: 99%